COMMUNITY OF PRACTICE (CoP) PADA PT. PUTRA KARANGETANG DI DESA POPONTOLEN KECAMATAN TUMPAAN KABUPATEN MINAHASA SELATAN - Indry M. Masinambow; Leonardus R. Rengkung; Agnes E. Loho (Sam Ratulangi University, 2016)
The objective of research is to analyze Community of Practice based on the elements of Domain/share repertoire, Community/Mutual Engagement, and Practice/share repertoire as factors of PT. Putra Karangetang. This research was conducted from November 2015 until January 2016, started from preparation until report compilation. The data used in the form of primary data. This research was carried out with Stratified random sampling technique. In which 40 members of a population. Data analysis was done descriptively using a likert scale. The result showed that those elements of Domain/share repertoire, Community/Mutual Engagement, and Practice/share repertoire are strong elements as forming factor in the Community of Practice of official employee PT. Putra Karangetang, the result showed 93,37% . Domain is the identity that has been set with particular interest that membership implies commitment, domain shaping up to be a collection of friends or network connections to achieve the goals of sustainable. Community as a means to gather people who share a common interest and engaged in discussions, they share knowledge and learn together. Practice as a process to improve skills, employees not only work in general but also share methods, techniques and experience to form a pattern of behavior and improve the skills of employees.